Seismic Structure of the Upper Mantle Beneath Eastern Asia From Full Waveform Seismic Tomography. (22nd August 2018) - Tao, Kai; Grand, Stephen P.; Niu, Fenglin
Abstract: To better understand the subsurface behavior of subducting slabs and their relation to the tectonic evolution of the overriding plate, we conduct a full waveform inversion on a large data set to determine a high‐resolution seismic model, FWEA18 ( Full Waveform inversion of East Asia in 2018 ), of the upper mantle beneath eastern Asia. FWEA18 reveals sharper, more intense high‐velocity slabs in the upper mantle under the southern Kuril, Japan, and Ryukyu arcs, than previous studies have found. The subducting Pacific plate is imaged as a roughly 100 km thick high‐velocity slab to near 550 km depth indicating relatively little deformation. Stagnation near 600 km depth is observed over horizontal distances of 600 km or less. The Pacific plate we image accounts for roughly 25 Myr of subduction with older slab likely located in the lower mantle. The Philippine plate, subducting beneath the Ryukyu Islands, has a clear termination at about 450 km depth. This may indicate a tearing event in the past or that less Philippine Sea plate has subducted than previously thought. We found a double‐layer high‐velocity anomaly above and below 660 km under the Yellow Sea and eastern coast of North China. This may correspond to parts of the Philippine Sea plate that detached in the past and Pacific plate that have intersected at depth or a complicated behavior of the Pacific plate at that depth. Slow cylindrical anomalies cross the entire upper mantle are imaged beneath major Holocene volcanoes, which are likely upwellings associated with the edges of deep slabs that are entering the lower mantle. Key Points: High‐resolution 3‐D full waveform inversion for P‐velocities and S‐velocities reveals sharper and more intense mantle structures beneath East Asia Subducting Pacific and Philippine Sea plates show little deformation until 550 km depth where the slabs stagnate and thicken Narrow cylindrical slow anomalies beneath major Holocene volcanoes are rooted adjacent to where deep slabs enter the lower mantle